How to Pick a Mate: The Guide to a Happy Marriage - Adams, Clifford R. (Clifford Rose), 1902-1987; Packard, Vance, 1914-1996 (Salt Lake City, UT : Project Gutenberg, 2022)
"How to Pick a Mate: The Guide to a Happy Marriage" by Dr. Clifford R. Adams and Vance O. Packard is a guide on marriage and mate selection written in the mid-20th century. The book aims to provide practical advice and insights based on research about the characteristics of successful marriages and the selection of partners. The authors explore emotional maturity, societal pressures, and individual expectations in the context of romantic relationships, ultimately emphasizing the importance of informed decision-making in love and marriage. At the start of the book, the foreword sets the stage for the authors' exploration of matrimony, highlighting the prevalence of marital difficulties and divorces, which underscores the necessity of sensible approaches to mate selection. The first chapter poses the question "Why marry, anyhow?" and provides an overview of societal trends regarding marriage, including the reasons why some people avoid it. The discussion touches on topics such as emotional readiness, the impacts of past relationships, and societal expectations, painting a comprehensive picture of what influences individuals when considering marriage. The opening emphasizes that while love is a universal desire, the pathways to achieving it can be fraught with challenges and misconceptions. (This is an automatically generated summary.)
Release date is 2022-02-22
hekula03, Tim Lindell and the Online Distributed Proofreading Team at https://www.pgdp.net (This book was produced from images made available by the HathiTrust Digital Library.)
Keywords: Marriage